2018
DOI: 10.1007/s10147-018-1260-0
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in medical therapy for metastatic urothelial cancer

Abstract: Cytotoxic chemotherapy has been the mainstay of medical therapy for metastatic urothelial cancer. Currently, the gemcitabine/cisplatin regimen is widely used worldwide as the standard first-line medical treatment. Very recently, in 2017, pembrolizumab, a highly selective, humanized monoclonal IgG4κ isotype antibody against programmed death 1, was approved as a second-line treatment to be used after platina-based chemotherapy for metastatic urothelial cancer in Japan. Based on its promising anti-tumor efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 25 publications
0
39
0
Order By: Relevance
“…According to the National Comprehensive Cancer Network, pembrolizumab is the preferred second-line therapy for patients with advanced/metastatic bladder cancer and may also be recommended as first-line therapy for patients whose tumors express PD-L1 CPS ≥ 10 or who are ineligible to receive platinum-based therapy [23]. Pembrolizumab is approved for second-line treatment of patients with advanced/metastatic UC in Japan [12]; however, there are no clear guidelines on choosing second-line therapy for these patients. In clinical practice, a variety of combination and single-agent therapies are prescribed [9,10,28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the National Comprehensive Cancer Network, pembrolizumab is the preferred second-line therapy for patients with advanced/metastatic bladder cancer and may also be recommended as first-line therapy for patients whose tumors express PD-L1 CPS ≥ 10 or who are ineligible to receive platinum-based therapy [23]. Pembrolizumab is approved for second-line treatment of patients with advanced/metastatic UC in Japan [12]; however, there are no clear guidelines on choosing second-line therapy for these patients. In clinical practice, a variety of combination and single-agent therapies are prescribed [9,10,28].…”
Section: Discussionmentioning
confidence: 99%
“…The potential of immunotherapy in bladder cancer treatment has been known for approximately 30 years, since the efficacy of using intravesical bacillus Calmette-Guérin to provoke an immune response to treat certain types of bladder cancer was identified [11]. Programmed death ligand 1 (PD-L1) expression on tumor cells can suppress immune responses against tumors by binding to programmed death 1 (PD-1) receptors on T cells [11,12]. Monoclonal antibodies against this pathway have been developed to promote antitumor immune responses in patients with advanced or metastatic cancers; results of phase 1/2 studies showed that monoclonal antibodies have promising efficacy and manageable tolerability in management of UC [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pembrolizumab, a humanized monoclonal antibody that targets programmed death receptor-1, was associated with a significant overall survival (OS) benefit when compared with docetaxel, paclitaxel and vinflunine in the second-line treatment of metastatic UC in the Phase III trial KEYNOTE-045 (4). Since December 2017, pembrolizumab has been approved in Japan as a second-line treatment for radical unresectable UC that has become exacerbated after chemotherapy (5). However, cisplatin-based systemic chemotherapy is still the gold-standard approach for patients with advanced or metastatic UC in the first line (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%